Affect and "normality" in GDR LGBT autobiography 1980-1990 - Osborn, S.A. (2018)
Autobiography provides the reader with an understanding of the experience of the GDR in a way which is not possible for a historical study. Historical narratives centre on the macro level of society and the political interactions between the individual and the state, the boundaries drawn between East and West, and the assertion of power in an effort to maintain stability. By contrast, personal narratives focus on the micro level of experience and emotion, but this is in response to the events which form the social and historical context.